Construction of Macroeconomic Variables on Financial Inclusion in Indonesia - Abdul Wahab; Qarina Qarina; Alim Syariati; Muhammad Dwi Aprinandhi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to determine the construction of macroeconomic variables and the level of financial inclusion in Indonesia. The variables in this study are the Gini ratio, poverty, economic growth (GDP), and the open unemployment rate as independent variables and financial inclusion as the dependent variable. The analysis technique is in the form of panel data regression using the best model of the three panel data regression models, namely the common effect model, fixed effect model, and random effect model. The model chosen based on the results of the Hausman test and Chow test is a random effect model. The value of the coefficient of determination is 21.6%. By using a random effects model that was processed using the Eviews 12 program, the results obtained that the Gini ratio variable had a positive and insignificant effect on financial inclusion, the percentage of poor variable had a negative and significant effect on financial inclusion, the variable economic growth (GDP) had a positive and significant effect on financial inclusion, The open unemployment rate variable has a negative and significant effect on financial inclusion.